Experiments link competition and climate change responses. (March 2016) - Alexander, Jake M.
Abstract: Species interactions can have a larger impact on plant performance than direct effects of climate change itself, as shown by Rysavy et al. in this issue of the Journal of Vegetation Science . Their study illustrates different ways in which plant–plant interactions can change following climate change, stressing the need for experiments to disentangle direct and indirect impacts of climate change. Abstract : Species interactions can have a greater impact on plant performance than direct effects of climate change itself, as shown by Rysavy et al. in this issue of the Journal of Vegetation Science . Their study illustrates different ways in which plant‐plant interactions can change following climate change, stressing the need for experiments to disentangle direct and indirect impacts of climate change.